2015
DOI: 10.1002/pc.23743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybridization on the mode II fracture toughness properties of flax/vinyl ester composites

Abstract: In this study, flax fiber reinforced and flax/basalt hybridized vinyl ester composites were produced and their interlaminar fracture toughness (mode II) behavior was investigated using the three-point bend end-notched flexural (3ENF) testing. From the results, the average of the maximum values for each group of specimen obtained for critical strain energy release rate G IIC and stress intensity factor K II for flax/vinyl ester specimens were 1,940 J/m 2 and 134 kPam 0.5 . Similarly, G IIC and K II values recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This failure allows only the measurement of crack initiation IFT. Almansour et al observed an analogous behavior for woven flax/vinyl-ester [48] and non-woven flax mat/vinyl-ester [83], whereas Rajendran et al [66,67] reported a complete nonlinear load-displacement curve for woven flax/epoxy composites. The experience of the latter, likewise to their DCB tests, is in stark contrast with the observations of previously cited authors (Almansour et al) and many other authors [84][85][86].…”
Section: Mode II Interlaminar Fracture Toughnessmentioning
confidence: 96%
“…This failure allows only the measurement of crack initiation IFT. Almansour et al observed an analogous behavior for woven flax/vinyl-ester [48] and non-woven flax mat/vinyl-ester [83], whereas Rajendran et al [66,67] reported a complete nonlinear load-displacement curve for woven flax/epoxy composites. The experience of the latter, likewise to their DCB tests, is in stark contrast with the observations of previously cited authors (Almansour et al) and many other authors [84][85][86].…”
Section: Mode II Interlaminar Fracture Toughnessmentioning
confidence: 96%
“…The results showed that the critical strain energy release rate G C , was significantly higher for CSM laminates than hemp, jute and unreinforced polymer composites of 10.21, 1.84, 0.97 and 0.10 kJ m −2 , respectively at 20% fibre volume fraction. Almansour et al [26] highlighted that non-woven flax/basalt hybridised laminates improved the fracture toughness compared to non-woven flax composites without hybridisation using 3ENF testing.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In addition, there are no reported works on the effect of water absorption on the fracture toughness of NFRCs. Also, very few studies have been undertaken to improve the fracture toughness of NFRCs by chemical treatment (20,21) and fibre or matrix hybridisation (22)(23)(24). Li et al (20) have conducted the fracture toughness test to investigate the effects of fibre surface treatment of sisal fibre reinforced vinyl ester composites.…”
Section: Introductionmentioning
confidence: 99%